Pemberdayaan Skill dan Pengetahuan Kader Kesehatan Mengenai Penanganan Kegawatdaruratan Obstetri sebagai Upaya Menurunkan Nilai Angka Kematian Ibu (AKI) di Desa Cipadang Kecamatan Gedong Tataan Kabupaten Pesawaran - Ratna Dewi Puspita Sari; Sutarto Sutarto; Winda Trijayanthi Utama (Penerbit Goodwood, 2023)
Purpose: The objectives of the implementation of this service activity are: maximizing the role and function of pregnant women cadres in Cipadang Village, Pesawaran Regency, strengthening the implementation of supervision of pregnant women cadres at the Pesawaran Regency level, and improving the quality of service and care in managing the anxiety of pregnant women during the COVID-19 pandemic in Pesawaran District. Method: The method used in the implementation of this activity is to provide counseling to the people of Cipadang Village which is carried out in two stages, namely the preparation stage and the implementation stage. The preparatory stage includes determining the target area, surveying the target area, partnering with partners, licensing the place, making the design of extension materials, and preparing the needs of cadres. While in the second stage, namely conducting a pre-test which aims to determine how far the knowledge of the participants about the topic to be given and a post-test to determine the increase in public understanding of the extension activities carried out. Results: Shows that the p-value is 0.000. This shows that there is a difference in the knowledge of the counseling participants before being given education and after being given education. Limitations: The article is only done in Cipadang Village, so socialization is needed in other villages in Pesawaran Regency. Contribution: This service activity is expected to provide scientific knowledge and skills to maternal cadres regarding the management of anxiety for pregnant women during the COVID-19 pandemic at the Pesawaran Regency community level.